Answer:
-(5 n + 6)
Step-by-step explanation:
Simplify the following:
-4 (n + 1) - (n + 2)
-4 (n + 1) = -4 n - 4:
-4 n - 4 - (n + 2)
-(n + 2) = -n - 2:
-4 - 4 n + -n - 2
Grouping like terms, -4 - 4 n - 2 - n = (-4 n - n) + (-4 - 2):
(-4 n - n) + (-4 - 2)
-4 n - n = -5 n:
-5 n + (-4 - 2)
-4 - 2 = -(4 + 2):
-5 n + -(4 + 2)
4 + 2 = 6:
-5 n - 6
Factor -1 out of -5 n - 6:
Answer: -(5 n + 6)
Answer:
D
Step-by-step explanation:
I hope this helps you out!
John's Bar 60 km away from Ben's Bar.
Doug's Bar is 40 km away from Kieran's Bar
John's Bar is 10 km nearer to Doug's Bar than Kieran's Bar
If I am to assume that these bar are in a liner position,
Ben's Bar Kieran's Bar John's Bar Doug's Bar
************* 60km*******************
*****************40 km ********************
*********30 km**************
Doug's Bar is 90 km away from Ben's Bar.
Ben to John = 60 km
John to Doug = 30 km
Ben to Doug = 60 + 30 = 90 km.
Answer: Im tying to figure it out but i cant sorry do youre best
Step-by-step explanation:
DO IT
The table isn’t shown so I cant tell